Extrinsic Factors Strong Motivators for Nurses in the Tertiary Care Hospitals - Shahnaz Dar; Nosheen Zehra; Farah Ahmad (ziauddin University, 2024)
Background: Motivation and job satisfaction ultimately effect work performance of an individual. There are various factors which influence the work motivation and knowledge of these factors can help in improving the work performance. Objective: To assess the different factors that are associated with work motivation among nurses working in private and public tertiary care hospitals of Karachi. Methods: This descriptive, cross-sectional study was carried out among nurses for duration of 3 months in 2013. Total 240 nurses from two tertiary care hospitals of Karachi were selected by convenience sampling. A pretested and self-administered questionnaire was used to assess factors associated with work motivation. Data was analyzed using SPSS version 20.0. Results: Of total 240 study participants, 48.8% (117) nurses were in favor of financial incentives that motivate them most. Salary structure and appraisal system both showed significant difference (p-value= 0.000) between nurses from public and private hospitals while the most content place to work was reported government hospitals by 43.4% (104) nurses. Work motivation mean score revealed significant difference (p-value =0.003) among nurses from different working areas of hospital. Factors associated with job satisfaction showed significant difference (p value = 0.000) among nurses from private and public sector hospitals. Conclusion: Financial incentives were found to be the most important motivating factor for nurses that improve their performance. It was also concluded that public sector hospitals along with so many factors of satisfaction are the most content place of working that motivate them most. Key Words: Motivation, Nurses motivation, Tertiary care hospital, factors of motivation.